Effects of Sheltering on Behavior and Fecal Corticosterone Level of Elderly Dogs - Uetake, Katsuji; Yang, Chu Han; Endo, Aki; Tanaka, Toshio (Frontiers in Veterinary Science, 2016)
In Japan, the human population is aging rapidly, and the abandonment of dogs by the elderly people who have died or been hospitalized becomes a problem. It is hypothesized that elderly dogs have difficulty adapting to the novel circumstances when brought to an animal shelter. Therefore, the objective of this study was to assess stress levels and demonstrate stress responses of elderly dogs just after admission to an animal shelter. As stress indicators, fecal corticosterone levels and changes in the ethogram of the dogs were investigated during the first week of admittance. Fecal corticosterone levels (mean ± SE) stayed high during the first week of residence, although they fell gently from the day after admittance (16650.1 ± 3769.7 ng/g) to the seventh day (12178.4 ± 2524.4 ng/g) (P <0.001). The proportions of behavioral expressions changed as the days passed (P < 0.001). In particular, stereotypies decreased from 35.7% on the first day to 2.6% on the sixth day, and time spent sleeping increased from 0.0% to 42.7%. These results indicate that elderly dogs admitted to an animal shelter seem to behaviorally adapt themselves to their novel circumstances, but might be stressed even on the seventh day of residence.